FAKTOR –FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA (45-59) TAHUN DI WILAYAH KERJA PUSKESMAS TAMAN SARI KOTA PANGKALPINANG (JURNAL SMART ANKES, 2021)
Hypertension occurs when elderly people’s systolic and diastolic blood pressure reaches more than 140 mmHg and 90 mmHg respectively. The data from Tamansari Community Health Center show the elderly’s hypertension cases for the last three years. In 2017, 441 cases (39.2%) were counted and 570 cases (41.9%) were identified in 2018. In 2019 the hypertension case soared accounted for 839 cases (46.15%). Based on the data, this research aims to identify the factors associated with hypertension in elderly people in the working area of Tamansari Community Health Center, Pangkalpinang City, 2020. This research used a cross-sectional design in the working area of the Tamansari Public Health Center in 2019, with a population of 580 elderly hypertension patients (45-59 years old). The sample was taken using a simple random sampling technique; meanwhile, the proportion of a proportion was used for determining the sample size from three urban villages in the Taman Sari Public Health Center working area. The results showed that there were factors associated with hypertension in elderly people aged 45-59 years, namely Gender (p = 0.002, POR = 4.857), Obesity (p = 0.018, POR = 3.011), Physical Activity (p = 0.005, POR = 3.909), smoking habits (p = 0.001, POR = 5.667), and salt consumption (p = 0.022, POR = 2.907). It can be concluded that smoking is amajor factor associated with hypertension in elderly people. Health workers are advised to be more proactive in providing information about hypertension to the public. Therefore, older citizens become more active and motivated to prevent hypertension by avoiding smoking and receiving counseling from the public health center. Accordingly, they know the factors causing hypertension and the ways to prevent hypertension conveyed by the existing health workers.